Youth Perspectives on Sexuality Communication With Parents and Extended Family. Issue 3 (31st March 2018) - Grossman, Jennifer M.; Richer, Amanda M.; Charmaraman, Linda; Ceder, Ineke; Erkut, Sumru
Abstract : Objective: To explore extended‐family sexuality communication and compare it with parent sexuality communication. Background: Family communication about sex can protect teens from sexual risk behavior. However, most studies on this topic focus exclusively on the parent–teen dyad; few capture the broader context of teens' family communication. Method: Using a mixed‐methods approach, a convenience sample of 22 teens from diverse racial and ethnic backgrounds were interviewed. Participants were asked to identify family members with whom they talk about sex and relationships, topics discussed, messages shared, and the teens' comfort talking about sex and relationships. Thematic analysis was used to explore participants' shared meanings and experiences. Results: Eighty‐six percent of teens reported talking with both parents and extended family about sex. Teens were more likely to report that parents than extended family shared messages about delaying sex and avoiding teen pregnancy and gave advice or shared information about sex. Teens were more likely to view extended family than parents as easy to talk with and as having shared life experiences, and some reported avoiding talk with parents about issues related to sexuality due to feeling awkward or fearing a negative reaction. Conclusion: Extended family may play a somewhat different role than parents in teens' sexuality communication, but family members showed a largely common set of family values. Implications: Extended family may be a valuable teen resource for sexuality communication, particularly when teens feel uncomfortable talking with parents.